Notary's Responsibility for the Deed of Transfer of Customary Heirs Without the Consent of All Heirs - Davina Malem Peraten Ketaren; Faisal Santiago (PT. ALHAFI BERKAH INDONESIA, 2025)
Legal certainty is a fundamental principle in every legal act, including in the making of authentic deeds by a notary. In the practice of inheritance based on customary law, such as in the Balinese indigenous people, there is often a transfer of inheritance by the holder of the purusa right without involving all the heirs, which is considered valid according to the customary provisions. However, when the notary pours the transfer into the form of an authentic deed without verifying the consent of all heirs, serious problems arise regarding the guarantee of legal certainty. Authentic deeds that should provide protection and strong evidence actually become vulnerable to lawsuits and lose legal force. This has the potential to violate Article 1320 and Article 1338 of the Civil Code regarding the legal conditions of the agreement, and is contrary to Article 16 paragraph (1) letters a and c of Law Number 2 of 2014 concerning the Notary Position which requires notaries to act carefully and impartially. This study aims to examine the extent to which legal certainty can be maintained in the making of customary inheritance transfer deeds that do not involve all heirs, as well as how the responsibility of notaries in such conditions. The research method used is normative juridical with a regulatory approach and case studies. The results of the study show that legal certainty can only be guaranteed if the notary makes the principle of prudence the main reference, including by ensuring that there are no objections from the right parties. In conclusion, the legal certainty of authentic deeds in the context of customary inheritance is highly dependent on the integrity of the notary in bridging customary law values and positive law in a balanced and objective manner.